Lipoprotein(a), high-sensitivity c-reactive protein, homocysteine and cardiovascular disease in the Multi-Ethnic Study of Atherosclerosis - Sarah O. Nomura; Harpreet S. Bhatia; Parveen K. Garg; Amy B. Karger; Weihua Guan; Jing Cao; Michael D. Shapiro; Michael Y. Tsai (American Journal of Preventive Cardiology)
Background and aims: Elevated lipoprotein(a) [Lp(a)], high-sensitivity C-Reactive Protein (hs-CRP), and total homocysteine (tHcy) are associated with atherosclerotic cardiovascular disease (ASCVD) risk. This study investigated the individual and joint associations of Lp(a), hs-CRP and tHcy with coronary heart disease (CHD) and stroke. Methods: This study was conducted in the Multi-Ethnic Study of Atherosclerosis (MESA) cohort (2000–2017) (CHD analytic N = 6,676; stroke analytic N = 6,674 men and women). Associations between Lp(a) (<50 vs. ≥50 mg/dL), hs-CRP (<2 vs. ≥2 mg/L) and tHcy (<12 vs. ≥12 µmol/L) and CHD and stroke incidence were evaluated individually and jointly using Cox proportional hazards regression. Results: Individually, elevated tHcy was associated with CHD and stroke incidence, Lp(a) with CHD only and hs-CRP with stroke only. In combined analyses, CHD risk was higher when multiple biomarkers were elevated [hs-CRP+Lp(a), hazard ratio (HR)=1.39, 95 % confidence interval (CI): 1.06, 1.82; hs-CRP+ tHcy, HR = 1.34, 95 % CI: 1.02, 1.75; Lp(a)+ tHcy HR = 1.58, 95 % CI: 1.08, 2.30; hs-CRP+Lp(a)+ tHcy HR = 2.02, 95 % CI: 1.26, 3.24]. Stroke risk was elevated when hs-CRP and either Lp(a) (HR = 1.51, 95 % CI: 1.02, 2.23) or tHcy (HR = 2.10, 95 % CI: 1.44, 3.06) was also high, when all three biomarkers were elevated (HR = 2.99, 95 % CI: 1.61, 5.58), or when hs-CRP and tHcy (HR = 1.79, 95 % CI: 1.16, 2.76) were both high. Conclusions: Risk of ASCVD was highest with concomitant elevation of tHcy, hs-CRP and Lp(a). Inclusion of tHcy and consideration of biomarker combination rather than individual biomarker levels may help better identify individuals at greatest risk for ASCVD events.